1972
DOI: 10.1136/jcp.25.7.570
|View full text |Cite
|
Sign up to set email alerts
|

The influence of spleen size on the distribution of red cells and plasma

Abstract: The red cell mass, splenic red cell pool, and plasma volume have been measured in a series of 64 patients with splenomegaly due to haematological disorders. In 45 patients the total blood volume was increased, this being due to expansion of the plasma volume which was closely correlated with spleen size. There was no significant relationship between the red cell mass and spleen size but the splenic red cell pool increased with increasing spleen size. In 12 patients serial estimations were made whilst changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…With gross enlargement of the spleen in chronic liver disease a large pool of erythrocytes may be sequestered in the spleen thus reducing the effective extrasplenic red cell volume (Donaldson, McArthur, MacPherson, and Richmond, 1970). Finally there is the possibility that the splenic enlargement per se might be associated with an expansion of the plasma volume to give a haemodilutional anaemia (Toghill and Green, 1972).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With gross enlargement of the spleen in chronic liver disease a large pool of erythrocytes may be sequestered in the spleen thus reducing the effective extrasplenic red cell volume (Donaldson, McArthur, MacPherson, and Richmond, 1970). Finally there is the possibility that the splenic enlargement per se might be associated with an expansion of the plasma volume to give a haemodilutional anaemia (Toghill and Green, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Haematocrit levels were determined in duplicate with Wintrobe tubes, allowance being made for plasma trapping (Chaplin and Mollison, 1952). Erythrocytes were labelled with 80-100 ,uCi sodium chromate (Na251CrO4) and measurements of red cell mass and splenic red cell pool were made using themethods described earlier (Toghill and Green, 1972). The red cell survival was expressed as the time in days for 50% loss of 51Cr from the circulating red cells (Tso51Cr).…”
Section: Methodsmentioning
confidence: 99%
“…In reports of two groups of patients with miscellaneous disor ders associated with splenomegaly a statistical relationship has been es Discussion tablished between pool size and spleen size [4,12]. However, P ettit et al [8], who measured total splenic red cell content, found it to be less in the lympho-proliferative disorders as compared with the myelo-proliferative diseases and regarded this as being due to replacement of the splenic cords by lymphoid tumour tissue.…”
Section: Splenic Pool Size In Myelo-and Lympho-proliferative Syndromesmentioning
confidence: 99%
“…It is possible that other factors associated with high‐altitude ascent influenced the spleen size reductions. For example, both plasma volume and nitric oxide change with ascent to high altitude (Beall et al., 2012 ; West, 2004 ), both of which have been found to influence spleen size at sea‐level (Engan et al., 2020 ; Toghill & Green, 1972 ).…”
Section: Introductionmentioning
confidence: 99%